Sistem Klasifikasi Mutu Air PDAM berdasarkan Zat Terlarut, PH dan Turbidity menggunakan Metode Fuzzy Sugeno berbasis Arduino - Fatchullah Wahid Afifi; Hurriyatul Fitriyah; Eko Setiawan (Fakultas Ilmu Komputer (FILKOM), Universitas Brawijaya, 2021)
Some characteristics of clean drinking water are fresh water, colorless and not smoky. One of the water sources that are considered clean and worth drinking is through PDAM (Perusahaan Daerah Air Minum). Water from PDAM was chosen because it has gone through various physical and chemical processes, so that PDAM-assisted water is considered clean enough to be used for daily needs in the future. Factors that affect the level of water feasibility are usually determined from the mixed content of the water. One of the ingredients used by PDAM is chlorine as a disinfectant to maintain water cleanliness and protect from bacteria. Referring to the Regulation of the Minister of Health of the Republic of Indonesia 492 / MENKS / PER / IV / 2017, the upper limit of chlorine content in drinking water is 5 mg / L. Water quality classification system designed by utilizing pH sensors to know the acidity level in water, turbidity sensors to know the level of turbidity in water, and TDS sensors to know the amount of dissolved substance content in water. Then the system will store and process input data from the sensor using the fuzzy method of takagi-sugeno model to classify water quality based on its content into three groups, namely safe, processed and dangerous. During the testing phase of the system, from 4 experiments with 3 PDAM water samples, the accuracy rate obtained from the system and compared to existing tools was 100%.